Materiales compuestos en arquitectura recursos e impacto ambiental (2014)
The article takes the topic of Composite Materials for its application in architecture and emphasizes two aspects: 1. definition, classification, mechanical and thermal properties, and uses in architecture of Composite Materials; and 2. life cycle analysis of some of the raw materials that make up. It seeks to establish whether the Composite Materials, to be included in the architectural projects, contribute to reducing the environmental impact caused by the construction industry or whether, on the opposite, provide greater environmental pollutants loads. It explores three kinds of composite materials: metal matrix, ceramic matrix and organic matrix. For the life cycle assessment, SimaPro software is used. It is concluded that the organic matrix composite materials, generate low environmental impact; the ceramic matrix, medium impact; and the metallic matrix, high impact.